2000
DOI: 10.1038/sj.ijo.0801260
|View full text |Cite
|
Sign up to set email alerts
|

Common apolipoprotein A-IV variants are associated with differences in body mass index levels and percentage body fat

Abstract: OBJECTIVE: To determine the relationship between two common apoA-IV variants (Thr 347 ?Ser; Gln 360 ?His), and body mass index (BMI) and percentage body fat. DESIGN: Cross-sectional study. SUBJECTS: Eight-hundred and forty-eight subjects screened for participation in ongoing clinical studies. MEASUREMENTS: ApoA-IV genotype, body mass index, waist-to-hip ratio and percentage body fat by bioelectric impedance. RESULTS: Participants had an average age of 41 AE 12 y and an average BMI of 28.2 AE 5.5 kgam 2 . Indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 59 publications
0
18
0
1
Order By: Relevance
“…Given that apoA-IV might modulate intestinal lipid absorption efficiency under conditions of high dietary fat intake, it is interesting that the apoA-IV T347S and Q360H polymorphisms, which are known to have an impact upon protein structure (56), postprandial triglyceride metabolism (57), and cholesterol absorption (58), have been found in epidemiological studies to be associated with a lower body mass index (Q360H) (5,59) or increased body mass index and adiposity (T347S) (5). This raises the possibility that these genetic polymorphisms might affect intestinal lipid absorption and thus could have important implications for the functional genomics of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that apoA-IV might modulate intestinal lipid absorption efficiency under conditions of high dietary fat intake, it is interesting that the apoA-IV T347S and Q360H polymorphisms, which are known to have an impact upon protein structure (56), postprandial triglyceride metabolism (57), and cholesterol absorption (58), have been found in epidemiological studies to be associated with a lower body mass index (Q360H) (5,59) or increased body mass index and adiposity (T347S) (5). This raises the possibility that these genetic polymorphisms might affect intestinal lipid absorption and thus could have important implications for the functional genomics of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Although a broad spectrum of physiological functions have been proposed for apoA-IV (5,6), the preponderance of evidence suggests that its primary biological function is related to intestinal lipid absorption. In humans, apoA-IV expression is restricted to the intestine and is specifically stimulated by triglyceride absorption (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…In human obesity, apoA-IV protein polymorphisms were reported to be associated with differences in body mass index and percentage of body fat and with the response of HDL levels to weight reduction. [12][13][14] In leptin receptor-deficient obese rats and in leptin-deficient obese mice, the expression of the apoA-IV gene is enhanced and its dietary regulation is altered. 15,16 Recently, Verges et al 17 reported that in obese patients fasting plasma apoA-IV is significantly elevated and postprandial plasma apoA-IV is markedly increased.…”
Section: Introductionmentioning
confidence: 99%
“…These genetic variants have been the subject of several association studies with lipid and lipoproteins, [18][19][20][21][22] but association studies with body weight and body fat parameters are scarce. 22,23 In this study, we aim to observe the effects of these APOA-IV polymorphisms on obesity and body fat distribution in subjects randomly sampled from a southern Brazilian community of European ancestry. Because our understanding of how environmental variables interact with genetic factors is incomplete, we also investigated the possibility of an interactive effect between genotype and smoking, alcohol consumption, and physical activity on body weight and body fat distribution.…”
Section: Introductionmentioning
confidence: 99%